National and Official Language: The Long Journey of Indonesian Language - Ridwan, Muhammad (Budapest International Research and Critics University, 2018)
Indonesia is a big country with more than 18,000 islands. It has at least 726 regional languages, making it the Worldâ€™s second most diverse, after Papua New Guinea. To choose one national and official language is a big problem for Indonesia because of the diversity of the regional languages. Given the diversity of cultures and vernaculars of our country, it was difficult to find what Indonesians had in common. That common identity would eventually be found by developing standardizing language to unify the islands. Â This paper will discuss the process of selecting Malay language became Indonesiaâ€™s national and official language. This is very important because national and official language will show the unity of a nation, especially during the colonization.